A dinâmica das organizações turísticas e o consumo de água em São Luis (MA) e Belém (PA) - GOMES, Eduardo Lima dos Santos (Universidade Federal do Pará, 2018)
This thesis discusses the limits and possibilities of the natural water resource to become an opportunity of competitive advantage in the tourism sector, particularly in tourist accommodation organizations. From this perspective, questions arise about the place and role of these tourist organizations in the political and socioenvironmental water scenario. Therefore, the objective was to analyze the extent to which the implications of water consumption position the tourist organizations of accommodation, in São Luís (MA) and Belém (PA), the formulation of sustainability strategies for eco-innovation. For this purpose, the study is based on a review of the literature on theories that explain economic development from a Schumpeterian and Neoschumpeterian view, as well as the approach to sustainable development on the path to water sustainability in the tourism sector. Based on the literature review, a hypothesis was suggested and tested in the empirical part of the thesis through an analysis of the dynamics of tourism organizations concerning the implications of water consumption in these two amazonian cities in question. The methodology had the interdisciplinary orientation between economics and anthropology, through the development of qualitative research of an exploratory, descriptive and explanatory type with the procedure of the case study of multiple character. For this, the technique of semi-structured interview with the application of the instrument form was used. This analysis is based on data obtained through interviews-formulary aimed at chief executives of the tourism organizations and water companies. The results show that the strategies adopted by tourism organizations are merely palliative measures directly proportional to the optimization of financial costs. With this, the water issue, especially in the face of the possibilities of a growing water crisis, becomes important for research and, in the tourism sector, water can be an opportunity for sustainability strategy for eco-innovation, promoting the responsible and smart tourism.